Answer:
Your answers are below ↓
Explanation:
Given ↓
A) 2x-3y = 5 and 3x+4y = 6 ( The method this has to be solved in is the elimination method. )
Now using these,
(1)×3 - (2)×2 = 6x + 9y - 6x - 8y = 15 - 12
therefore,
y = 3
putting the value of y in eqn. (1)
2x + 6 = 5
therefore,
x = -1/2
B) y=x^2 - 2x and y = 2x -3 ( The method this has to be solved in is the substitution method. )
Reduce the greatest common factor on both sides of the equation:
![\left \{ {{4x-y=9} \atop {xy=-2}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/jk96o0hra0yrh9ge0ywblruaf5hrrsrz5u.png)
Rearrange like terms to the same side of the equation:
![\left \{ {{-y=9-4x} \atop {xy=-2}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/ba0xquw90ej6de0vnjhmux8ezdkd6qd2zm.png)
Divide both sides of the equation by the coefficient of the variable:
![\left \{ {{y=-9+4x} \atop {xy=-2}} \right.](https://img.qammunity.org/2023/formulas/mathematics/college/wad1eapb1ye7qp8sbrvvdih6qukgjklcqa.png)
Substitute the unknown quantity into the elimination:
![x(-9+4x)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/u4x09nhatdzhi2ogeiyk8q4yx5jh5la4zk.png)
Apply Multiplication Distribution Law:
![-9x+4x^2=-2](https://img.qammunity.org/2023/formulas/mathematics/college/pyvzmmpt3p24l05w1nh3jazw1b3fl6yla9.png)
Reorder the equation:
![4x^2-9x=-2](https://img.qammunity.org/2023/formulas/mathematics/college/r9z51jofvpk25rxvplv9c4a4lr589wdy4q.png)
Divide the equation by the coefficient of the quadratic term:
![(1)/(4)(4x^2)+(1)/(4)(-9x)=(1)/(4)*(-2)\\](https://img.qammunity.org/2023/formulas/mathematics/college/3sfl08mhjwre0cc2sue4eebdt0lxs157ec.png)
Calculate:
![x^2-(9x)/(4)=-(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/k9z4kxx8str8zk11ej4bk11i8oq07qcbuw.png)
Add one term in order to complete the square:
![x^2-(9x)/(4)+((9)/(4)*(1)/(2))^2=-(1)/(2)+((9)/(4)*(1)/(2))^2](https://img.qammunity.org/2023/formulas/mathematics/college/nphejl0mcl9r7ee4sf68kiivgnqubzh4u5.png)
Calculate:
![x^2-(9x)/(4)+((9)/(8) )^2=-(1)/(2) +((9)/(8) )^2](https://img.qammunity.org/2023/formulas/mathematics/college/q9qxi38pukxdblouhhq2btg39gncihsybl.png)
Factor the expression using
:
![(x-(9)/(8) )^2=-(1)/(2) +((9)/(8) )^2](https://img.qammunity.org/2023/formulas/mathematics/college/l4fubpakkp3k2nd58hgvlkf98ahy62iute.png)
Simplify using exponent rule with the same exponent rule:
![(ab)^n=a^n*b^n](https://img.qammunity.org/2023/formulas/mathematics/college/30zwwgtodpzyoli4h6tubm4r9x9w3fmso8.png)
![(x-(9)/(8) )^2=-(1)/(2) +(9^2)/(8^2)](https://img.qammunity.org/2023/formulas/mathematics/college/me27vhhp660dq6vdu2fjyiqy9xhg3pexd3.png)
Calculate the power:
![(x-(9)/(8) )^2=-(1)/(2)+(81)/(64)](https://img.qammunity.org/2023/formulas/mathematics/college/12qm1bv7okc86hi2uuxzt82psgf9lqd9az.png)
Find common denominator and write the numerators above the denominator:
![(x-(9)/(8) )^2=(-32+81)/(64)](https://img.qammunity.org/2023/formulas/mathematics/college/8tdp1vxk3g3jt3m73nwg3si6f6vuwj1t5w.png)
Calculate the first two terms:
![(x-(9)/(8) )^2=(49)/(64)](https://img.qammunity.org/2023/formulas/mathematics/college/ml3xh1zojjsqrw887uajil3uzka4g2vvj9.png)
Rewrite as a system of equations:
or
![x-(9)/(8) =-\sqrt{(49)/(64) }](https://img.qammunity.org/2023/formulas/mathematics/college/i6hjwpfgw268god9g6u7x4f68ma2y9yx7g.png)
Rearrange unknown terms to the left side of the equation:
![x=\sqrt{(49)/(64) } +(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/uzo1kqp2spb65gjmntcl9qrv4xhnuhhf34.png)
Rewrite the expression using
:
![x=(√(49) )/(√(64) ) +(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/93s00sgmmhjgnr1rk8c96x8salbiavxxsm.png)
Factor and rewrite the radicand in exponential form:
![x=(√(7^2) )/(√(8^2) ) +(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/kow0rrqxbqgv38nidtiknna7mdpjh1j7gp.png)
Simplify the radical expression:
![x=(7)/(8) +(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/q564bvme3c6r6ieymwtbrw8euqcx7g2w07.png)
Write the numerators over the common denominator:
![x=(7+9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/ez1vzk6oou2dcakz67djilr2bshlwisd1b.png)
Calculate the first two terms:
![x=(16)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/ybfnn29vdoy9d4q4cpl0socva4mmgr7f3l.png)
Reduce fraction to the lowest term by canceling the greatest common factor:
![x=2](https://img.qammunity.org/2023/formulas/mathematics/college/6ij5lvx45qkbn22ki7umkb6rdcr9rugcgd.png)
Rearrange unknown terms to the left side of the equation:
![x=-\sqrt{(49)/(64) } +(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/amylwy0hh1j5bi7kd2ed1efbv4h8k72k1b.png)
Rewrite the expression using
:
![x=-(√(49) )/(√(64) )+(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/lvwdch5r05v25db0mfsq8g2oc1o2j6dlgw.png)
Factor and rewrite the radicand in exponential form:
![x=-(√(7^2) )/(√(8^2) ) +(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/ghx0134dbvtd6n2k2ulpmmy540vlecn5ls.png)
Simplify the radical expression:
![x=-(7)/(8) +(9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/khjjykxkrg4okhcubhrhjncrh2hirur52c.png)
Write the numerators over common denominator:
![x=(-7+9)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/ol5luamcinlgw6cujaw513yqsngsfyya80.png)
Calculate the first two terms:
![x=(2)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/g6pfcczwj6wwfzsiiz9z8ltdh2xnrri3gx.png)
Reduce fraction to the lowest term by canceling the greatest common factor:
![x=(1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/rcgnf76psirgpl39paeie4ci2h496uwtsh.png)
Find the union of solutions:
or
![x=(1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/rcgnf76psirgpl39paeie4ci2h496uwtsh.png)
Substitute the unknown quantity into the elimination:
![y=-9+4*2](https://img.qammunity.org/2023/formulas/mathematics/college/qtpzi2twjd3adinujtqv5aqx4v615dac2l.png)
Calculate the first two terms:
![y=-9+8](https://img.qammunity.org/2023/formulas/mathematics/college/kkauixmz5oidti5uq0n3z6acthgaxqn9vq.png)
Calculate the first two terms:
![y=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/vwgcxbnu6slshz866yc5mzof7h9jqvl6lx.png)
Substitute the unknown quantity into the elimination:
![y=-9+4*(1)/(4 )](https://img.qammunity.org/2023/formulas/mathematics/college/82t680astix3e1ev8voc3jt12qx1yvrbiu.png)
Reduce the expression to the lowest term:
![y=-9+1](https://img.qammunity.org/2023/formulas/mathematics/college/dx82osj9sd5jv1l5gikgfd68u607a8bvw6.png)
Calculate the first two terms:
![y=-8](https://img.qammunity.org/2023/formulas/mathematics/high-school/iycofex0l0415of2uakh841374m7yri2qt.png)
Write the solution set of equations:
or
-------> Answer
C) y=x^2 - 2x and y = 2x -3 ( This method this has to be solved in is the substitution method. )
Step 1: We start off by Isolating y in y = 2x - 3
y=2x-3 ----------> ( Simplify )
y+(-y)=2x-3+(-y) ---- > ( Add (-y)on both sides)
0=-3+2x-y
y/1 = 2x-3/1 --------> (Divide through by 1)
y = 2x - 3
We substitute the resulting values of y = 2x - 3 and y = x^2 - 2x
(2 * x - 3) = x^2 - 2x ⇒ 2x -3 = x^2 - 2x ----> ↓
(Substituting 2x - 3 for y in y = x^2 -2x )
Next: Solve (2x - 3 = x^2 - 2x) for x using the quadratic formular method
2x - 3 = x^2 - 2x
x = -b±b^2-4ac/2a Step 1: We use the quadratic formula with ↓
a = -1,b=4,c= - 3
x = -4±(4)^2-4(-1)(-3)/2(-1) Step 2: Substitute the values into the Quadratic Formular
x = -4± 4/ - 2 x = 1 or x = 3 Step 3: Simplify the Expression & Separate Roots
x = 1 or x = 3 ------- ANSWER
Substitute 1 in for x in y = 2x - 3 then solve for y
y = 2x - 3
y = 2 · (1) - 3 (Substituting)
y = -1 (Simplify)
Substitute 3 for in y = 2x - 3 then solve for y
y = 2x - 3
y = 2 · (3) - 3 (Substituting)
y = 3 (Simplify)
Therefore, the final solutions for y = x^2 -2x; y = 2x - 3 are
x₁ = 1, y₁ = -1
x₂ = 3, y₂ = 3